O acesso à informação para a tomada de decisão estratégica: um modelo integrado de gestão da informação - Lima, Francisco Andson da Paz (2021)
The objective of this research is to understand how access to information can be used positively for strategic decision making in organizations, and based on the understanding achieved, create arguments that support the proposal for an integrated prototype model of Information Management. For that, the methodology used was the bibliographic review of the literature, all the researches were made in scientific databases from which the theoretical and epistemological inputs were obtained and the basis for the analysis of the technical processing of the information. The results obtained from the data analysis revealed that Information Management in systematized and structured processes, allows the information flow to subsidize the strategic decision-making process in organizations. It was also possible to propose an integrated prototype model for Information Management.